Second line treatment options for pancreatic cancer. (13th October 2017) - Passero, Frank C.; Saif, Muhammad Wasif
ABSTRACT: Introduction : Patients with advanced pancreatic cancer (APC) refractory to first-line therapy have a dismal prognosis and limited therapeutic options, with only one option consisting of nanoliposomal irinotecan in combination with fluorouracil and folinic acid which was approved by FDA based upon results of the phase III NAPOLI-1 study. Areas covered : We performed a literature search for relevant published clinical trials, abstracts of trials in progress and ongoing or planned trials for the second line treatment of APC using Pubmed.com, ClinicalTrials.gov and American Society of Clinical Oncology (ASCO) abstract search as sources. We present an in-depth analysis of the phase I-III clinical trials determining the role and efficacy of second-line treatment in patients with APC. We also describe ongoing studies and rationale for future investigation. Expert opinion : Despite advances in first-line therapy such as gemcitabine/nab-paclitaxel and FOLFIRINOX in APC, median overall survival remains less than 12 months, highlighting the need to develop second-line therapies. In order to establish much needed effective second-line treatment options, we need cooperative efforts among institutions and community practices in enrolling these refractory patients in clinical trials. It should be emphasized that in addition to chemotherapy options, all patients should have the opportunity to consult with nutritionist, social worker and palliative care health providers to assist with goals of care, symptom management and end of life discussions.